Developing online virtual tour for Faculty Computer and Mathematical Science (FSKM) / Mohd Iqbal Hazzard Ahmad Zaini - Ahmad Zaini, Mohd Iqbal Hazzard (2013)
This project focuses on a multimedia development approach to develop a virtual tour for faculty of computer and mathematical science (FSKM) to help new and existing student to find classroom and lecturer room location more easily with aided of virtual tour technology. There are three research objectives to be achieved. First objective are to identify suitable multimedia System Development Methodology for virtual tour. Second objective are to gathering the requirements and analyze the requirement. Third objective is to design the system and lastly is to develop the virtual Tour for FSKM. This virtual tour project describes class location in detail by providing specific location picture and student will be guide to reach the class destination aided by a series of picture. This virtual tour will be presented interactively by providing some navigation button as a part of user friendly system.